Transformation of Stroke Rehabilitation through Occupational Game Consoles: A Quasi-Experimental Study at RSUD Dr. Adhyatma, MPH, Semarang - Daniswari, Aruna; Azam, Mahalul; Rahayu, Sri Ratna (Universitas Negeri Semarang, 2025)
Stroke is a leading cause of long-term disability worldwide, often resulting in impaired motor function and reduced independence in daily activities. Innovative and engaging rehabilitation strategies are urgently needed to improve patient outcomes and adherence. This study aimed to evaluate the effectiveness of an occupational game console in improving functional abilities among stroke patients. A quasi-experimental study was conducted at RSUD Dr. Adhyatma, MPH, Semarang, between March and June 2024, involving 30 stroke patients aged 30–70 years. All participants completed in a 4-week rehabilitation program without a control group. They received structured therapy using an occupational game console designed to enhance motor coordination, muscle strength, and independence. Functional improvements were measured using the Barthel Index (BI), Manual Muscle Test (MMT), and Nine Hole Peg Test (NHPT). Data were analyzed using paired sample t-tests with a significance level set at p < 0.05. The participants included 18 males (60%) and 12 females (40%). Most were in the 51 60 years age group (40.0%), followed by 41–50 years (26.7%), and smaller proportions in 30–40 years (16.7%) and 61–70 years (16.7%). In term of stroke duration, 56.7% had experienced a stroke for 5–8 months, 23.3% for 0–4 months, and 20.0% for 9–12 months. The results showed significant improvements in functional outcomes, with BI scores increasing from 45 (moderate dependence) to 65 (mild dependence), MMT scores improving from 3/5 to 4/5, and NHPT times decreasing from 120 to 90 seconds (p < 0.01). Additionally, 85% of patients reported higher motivation and engagement due to the console’s interactive and gamified features. Occupational game consoles demonstrate promising potential as innovative and accessible tools to support stroke rehabilitation by enhancing motor function, independence, and patient engagement. Future studies should include randomized controlled trials with larger samples and longer durations to assess long-term effectiveness and broader clinical applications.